Dorsally and Ventrally Derived Oligodendrocytes Have Similar Electrical Properties but Myelinate Preferred Tracts - Tripathi, Richa B. (J Neurosci, 2011)
In the developing spinal cord, most oligodendrocyte precursors (OLPs) arise from the ventral ventricular zone (VZ) under the influence of Sonic Hedgehog, but a minority are generated from the dorsal VZ in a Hedgehog-independent manner. In the developing forebrain too, OLPs arise from both the ventral and the dorsal VZ. It is not known whether dorsally and ventrally derived oligodendrocyte (OL) lineage cells have different properties. We generated a dual reporter mouse line to color code ventrally and dorsally derived OLPs (vOLPs and dOLPs) and their differentiated oligodendrocyte progeny (vOLs and dOLs) for functional studies. We found that ∼80% of OL lineage cells in the postnatal spinal cord and ∼20% in the corpus callosum are ventrally derived. In both spinal cord and corpus callosum, vOLPs and dOLPs had indistinguishable electrical properties, as did vOLs and dOLs. However, vOLPs and dOLPs had different migration and settling patterns. In the spinal cord, vOLPs appeared early and spread uniformly throughout the cord, whereas dOLPs arrived later and remained mainly in the dorsal and dorsolateral funiculi. During adulthood, corticospinal and rubrospinal tracts became myelinated mainly by dOLs, even though vOLs dominated these tracts during early postnatal life. Thus, dOLPs are electrically similar to vOLPs but appear to outcompete them for dorsal axons.